STUDYING THE GROWTH AND PRODUCTIVITY OF SAFFRON UNDER DIFFERENT AGRICULTURE TECHNIQUES - Razan K; R. Aziz; K. Al-Maari; F. Al-biski (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted at Abi – Jarash farm, Damascus, Syria, during 2018/2019 and 2019/2020 growing seasons. The aim of this study was comparing the effect of three different cultivation techniques of saffron (Crocus sativus L.), which were soilless cultivation, within the nutrient film technique (NFT), and the technique of cultivation in substrates (mixture of peat moss- perlite), in addition to cultivation in soil. An increasing in the vegetative growth measurements was recorded with​​ cultivation saffron in the soil, compared to the cultivation without soil, within the nutrient film technology (hydroponics) ,and the technology of cultivation in the substrates (peat moss and perlite mixture)، Flowering was poor in the hydroponics technique, while non significant differences were observed among the cultivation technique in the peat moss–perlite mixture, and the cultivation in the soil in first and second seasons . Cultivation in the soil achieved a significant increase in the rate of corms multiplication (corm plant-1), and the weight of daughter corms produced from one plant, whereas, a qualitative superiority appeared within the nutrient film technique, in which the percentage of commercial corms (˃ 8 g) reached 100%, and the average weight of the produced corms was 13.65,16.07 g in first and second seasons, respectively .